BEHAVIORAL CONCEPTS IN FINANCIAL REPORTING: A LITERATURE REVIEW - Suwandi, Suwandi; Lambyombar, Yustinus; Eka, Andi Primafira Bumandava (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
Accounting practices in various companies still show behavior that violates ethics and financial fraud that harms stakeholders. This literature review research aims to examine behavioral accounting practices in financial reporting. The data collection method was carried out by searching for research journal articles according to the topic through Google Scholar searches. The collected data was then analyzed using content analysis techniques with stages of data extraction, data summarization, coding, and discussion and drawing conclusions. This study suggests that ethical management behavior in financial reporting can increase transparency, trust, and the long-term value of the company, while information disclosure and management of conflicts of interest encourage accountability, growth opportunities, and a reputation for professionalism. On the other hand, profit regulation can reduce trust, credibility and create unhealthy competitive pressure for the company. Following up on the results of this study, it is important to strengthen ethical practices in financial reporting, increase information transparency, manage conflicts of interest carefully to build trust, credibility, and minimize the risk of negative impacts on the company's reputation.